Best Answer

-3x + 6 = 12

Subtract 6 from each side:

-3x = 6

Divide each side by -3:

x = -2

More answers

3x + 6 = 12

Subtract 6 from each side:

3x = 6

Divide each side by 3:

x = 2

Q: 3x plus 6 equals 12

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3x + 2 = 3x + 6 This is not possible.

-3x + 2y = 12-3x + 3x + 2y = 3x + 122y = 3x + 122y/2 = 3x/2 + 12/2y = (3/2)x + 6

Multiply first equation by 1.5, giving 3x + 3y = 12, but we are told that 3x + 3y = 6. If there isn't an error in the question then 2 = 1!

4x2+3x+6+5x+3x+6 = 4x2+11x+12 when simplified

If: -3x+2y = 12 Then: y = 1.5x+6 in slope-intercept form

Related questions

6-3x+12=0 6+12-3x=0 18-3x=0 18=3x x=6

-3x + 6 = -30 -3x = -30 - 63x = 36x = 36/3Therefore, x = 12.

3x + 2 = 3x + 6 This is not possible.

3x+5y=48 5y=48-3x-3x+5y=12 -3x+(48-3x)=12-6x=-36x=65y=48-3(6)5y=30y=6(6,6)

3x + 2y = 12 ie 2y = 12 - 3x so y = 6 - 3x/2

3x + 6 = 12Subtract 6 from each side:3x = 6Divide each side by 3:x = 2

3x+12 = 18 3x = 18-12 3x = 6 x = 2

3x+y=6

-3x + 2y = 12-3x + 3x + 2y = 3x + 122y = 3x + 122y/2 = 3x/2 + 12/2y = (3/2)x + 6

Multiply first equation by 1.5, giving 3x + 3y = 12, but we are told that 3x + 3y = 6. If there isn't an error in the question then 2 = 1!

4x2+3x+6+5x+3x+6 = 4x2+11x+12 when simplified

If: -3x+2y = 12 Then: y = 1.5x+6 in slope-intercept form